Identifikasi Faktor Eksternal dan Internal Yang Mempengaruhi Perkembangan UMKM (Studi Kasus Pada Umkm di Kabupaten Magelang) - Lukas Dwi Febrian; Ika Kristianti (Journal of Economic, Management, Accounting and Technology (JEMATech), 2020)
This study aims to identify aspects in external and internal factors that influence the development of MSMEs in Magelang Regency. The data used are primary data obtained from questionnaires and surveys addressed to 100 respondents registered at the Department of Cooperatives, Small and Medium Enterprises with the result that only the social and economic aspects of external factors are proven to have a positive effect because most MSME actors are in areas with conditions the economy of the community is quite good and is in the area of ​​tourism potential so that social and economic aspects can increase sales and encourage business development. While on internal factors, only one aspect that has a positive effect is the capital aspect because most business actors when running their businesses tend to use their own capital rather than doing loans because they avoid various risks. Meanwhile, other aspects in external and internal factors do not have a positive effect because in general business actors have not yet managed their businesses by involving institutions and have not managed their businesses properly.